Cover Feature: Improved Electrochemical Performance of FeF3 by Inlaying in a Nitrogen‐Doped Carbon Matrix (ChemElectroChem 20/2019). Issue 20 (25th September 2019) - Li, Jia; Fu, Licai; Zhu, Jiajun; Yang, Wulin; Li, Deyi; Zhou, Lingping
Abstract : The Cover Feature illustrates doped nitrogen atoms that enhance the electron transport capability of a carbon matrix, thereby significantly improving the conductivity of FeF3. Furthermore, the doping sites with adsorption ability of Li + limit it to the vicinity of FeF3, thus ensuring the rapid operation of lithium storage. More information can be found in the Article by J. Li et al. on page 5203 in Issue 20, 2019 (DOI: 10.1002/celc.201901060 ).